2007
DOI: 10.1515/polyeng.2007.27.1.29
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Processability by Injection Molding of Abs/Pc Blends Obtained From Recycled Materials

Abstract: Injection molding of recycled thermoplastic materials is a possible alternative for the manufacture of new products and is becoming increasingly important in the industrial sector. Due to the ease with which recycled materials can be mixed, and as so little is known about the process characteristics required to obtain products in optimum conditions, this paper proposes an evaluation criterion for the processability of different blends of recycled materials (ABS/PC blends). With this aim in view, a multicriteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Larsson and Bertilsson (1995) blended recycled ABS with PC in order to increase impact strength and increase the flame retardant property, Garcia et al (2007) studied the compatibility of recycled ABS with recycled PVC obtained from credit cards. In order to improve the processability of recycled ABS, Reig et al (2007) blended ABS with Polycarbonate (PC), and Eguiazabal and Nazabal (1990) also demonstrated that ABS/PC blends improve the mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Larsson and Bertilsson (1995) blended recycled ABS with PC in order to increase impact strength and increase the flame retardant property, Garcia et al (2007) studied the compatibility of recycled ABS with recycled PVC obtained from credit cards. In order to improve the processability of recycled ABS, Reig et al (2007) blended ABS with Polycarbonate (PC), and Eguiazabal and Nazabal (1990) also demonstrated that ABS/PC blends improve the mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The recycled materials showed a significant increase of the elongation at break, while reprocessing did not affect the modulus and the tensile stress despite the likely occurring chain scissions due to thermal degradation. A similar approach was chosen for recycling PC/ABS blends (Reig et al 2007). In particular, the effect of the different variables was studied using a statistical model applied to an injection molding processing.…”
Section: With a Compatibilizing Methodsmentioning
confidence: 99%
“…El empleo de estos modelos supone pues la necesidad de determinar un total de siete paráme-tros (n, τ * , D 1 ,D 2 , D 3 , A 1 y A 2 ), algunos de cuyos valores se pueden predefinir, bien en base a estimaciones verificadas por diversos autores (Reig et al 2007, Reig et al 2005, Ferrándiz et al 2013, o bien por análisis directo de las características de los materiales. Por otro lado, para establecer los valores de viscosidad se realizan iteraciones de los parámetros dependientes junto a los valores obtenidos experimentalmente.…”
Section: Ajustes Al Modelo Reológicounclassified